Reproductive Output, Synchrony across Depth and Influence of Source Depth in the Development of Early Life stages of Kelp. Issue 1 (18th December 2020) - Giraldo‐Ospina, Ana; Kendrick, Gary A.; Hovey, Renae K.
Abstract : Ecklonia radiata is the main foundation species in Australian temperate reefs, yet little has been published on its reproduction and how this may change across its depth range (1–50+ m). In this study, we examined differences in sporophyte morphology and zoospore production during a reproductive season and across four depths (7, 15, 25, and 40 m). Additionally, we examined differences in germination rate, survival, and morphological traits of gametophytes obtained from these four depths, cultured under the same light and temperature conditions. Multivariate morphology of sporophytes differed significantly between deep ( 40 m) and shallow sites (7 and 15 m), but individual morphological traits were not significantly different across depths. Total spore production was similar across depths but the peak of zoospore release was observed in February at 15 m of depth (6, 154 zoospores · mm −2 of tissue) and the minimum observed in January at 7, 25, and 40 m (1, 141, 987, and 214 zoospores · mm −2 of tissue, respectively). The source depth of zoospores did not have an influence in the germination rate or the survival of gametophytes, and only gametophytes sourced from 40 m sites presented significantly less surface area and number of branches. Overall, these results indicate that E. radiata 's reproductive performance does not change across its depth range and that kelp beds reproducing in deeper areas may contribute to the replenishment of their shallow counterparts. We propose that deep kelps may constitute a mechanism of resilience against climate change and anthropogenic disturbances.